2020
DOI: 10.3390/ani10081327
|View full text |Cite
|
Sign up to set email alerts
|

Effects of High Intensity Laser Therapy in the Treatment of Tendon and Ligament Injuries in Performance Horses

Abstract: The aim of this study was to evaluate the effects of high intensity laser therapy (HILT) on tendon and ligament injury treatment in horses. Twenty six horses with tendinopathies were randomly assigned to a HILT treated or to a non-treated group. Each horse was subjected to the same rehabilitation programme. Horses from the treatment group underwent a series of fifteen HILT treatments with the same parameters. Clinical and ultrasound assessments were performed by the same veterinarian and were carried out befor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 33 publications
1
16
0
Order By: Relevance
“…In that study, improvement was found in the pain, swelling and lameness assessed after treatment in the group treated with HILT compared with the control group. Moreover, in ultrasound examination for lesion percentage reduction, there was a statistically significant improvement in the group treated with HILT in comparison with the control group [7]. Similar clinical results using HILT were described by Pluim et al [8], who treated tendinopathy and desmopathy with HILT or with HILT and other therapies on a group of 150 sport horses, but the study did not include a control group.…”
Section: Introductionsupporting
confidence: 67%
“…In that study, improvement was found in the pain, swelling and lameness assessed after treatment in the group treated with HILT compared with the control group. Moreover, in ultrasound examination for lesion percentage reduction, there was a statistically significant improvement in the group treated with HILT in comparison with the control group [7]. Similar clinical results using HILT were described by Pluim et al [8], who treated tendinopathy and desmopathy with HILT or with HILT and other therapies on a group of 150 sport horses, but the study did not include a control group.…”
Section: Introductionsupporting
confidence: 67%
“…Further, the average duration of the rehabilitation period was much shorter than described in previously published studies on different treatment modalities for tendinitis and desmitis in horses 10 . Beneficial effects were also reported in a recent study in 26 sports horses with tendinopathy or desmopathy that were randomly assigned to either high‐intensity laser therapy or a non‐treatment group 11 . In the treatment group, analgesic and anti‐inflammatory scores were better, lameness was improved and better lesion filling on ultrasound was found when compared to non‐treated horses 11 .…”
Section: Introductionmentioning
confidence: 68%
“…10 Beneficial effects were also reported in a recent study in 26 sports horses with tendinopathy or desmopathy that were randomly assigned to either high-intensity laser therapy or a non-treatment group. 11 In the treatment group, analgesic and anti-inflammatory scores were better, lameness was improved and better lesion filling on ultrasound was found when compared to non-treated horses. 11 A recent case report describes the successful application of a high-power laser to treat injuries of the medial collateral ligament of the carpus in two horses.…”
Section: Introductionmentioning
confidence: 86%
See 2 more Smart Citations